Characterizing the risk interplay between alcohol intake and body mass index on cirrhosis morbidity. Issue 2 (6th December 2021) - Innes, Hamish; Crooks, Colin J.; Aspinall, Esther; Card, Tim R.; Hamill, Victoria; Dillon, John; Guha, Neil I.; Hayes, Peter C.; Hutchinson, Sharon; West, Joe; Morling, Joanne R.
Abstract: Background and Aims: It is thought that alcohol intake and body mass index (BMI) interact supra‐additively to modulate the risk of cirrhosis, but evidence for this phenomenon is limited. We investigated the interrelationship between alcohol and BMI on the incidence of cirrhosis morbidity for participants of the United Kingdom Biobank (UKB) study. Approach and Results: The primary outcome was the cumulative incidence of cirrhosis morbidity, defined as a first‐time hospital admission for cirrhosis (with noncirrhosis mortality incorporated as a competing risk). All UKB participants without a previous hospital admission for cirrhosis were included in the analysis. We determined the ratio of the 10‐year cumulative incidence in harmful drinkers versus safe drinkers according to BMI. We also calculated the excess cumulative incidence at 10 years for individuals with obesity and/or harmful alcohol compared to safe drinkers with a healthy BMI of 20–25.0 kg/m 2 . A total of 489, 285 UK Biobank participants were included, with mean of 10.7 person‐years' follow‐up. A total of 2070 participants developed the primary outcome, equating to a crude cumulative incidence of 0.36% at 10 years (95% CI:0.34–0.38). The 10‐year cumulative incidence was 8.6 times higher for harmful (1.38%) versus safe drinkers (0.16%) if BMI was healthy. Conversely, it was only 3.6 times higher for obese participants (1.99% vs. 0.56%). Excess cumulative incidence was 1.22% (95% CI:0.89–1.55) for harmful drinkers with a healthy BMI, 0.40% (95% CI:0.34–0.46) for obese individuals drinking at safe levels, and 1.83% (95% CI:1.46–2.20) for obese harmful drinkers (all compared to safe drinkers with a healthy BMI). Conclusions: Alcohol intake and obesity are independent risk factors for cirrhosis morbidity, but they do not interact supra‐additively to modulate the cumulative incidence of this outcome.